Biologia e ecologia trófica de Hemiodus unimaculatus (Bloch, 1794) (Characiformes: Hemiodontidae) no Rio Araguari, na área de influência da Usina Hidrelétrica Coaracy Nunes, Amapá, Brasil - TRINDADE, Paulo Arthur de Abreu (Universidade Federal do Pará, 2014)
This research aims to contribute to the knowledge of biology and trophic ecology of the species H. unimaculatus in Araguari river, in the influence area hydropower Coaracy Nunes, Amapá, Brazil. The study region corresponds to a portion of the river basin Araguari. Samples were collected bimonthly from May 2009 to July 2010. Batteries were used for mesh networks (2, 2.5, 3, 4, 5, 6, cm between opposite knots with 10 m x 1.5 m in height) and casting net (15 and 20 mm). The gillnets were exposed during 17 h, with inspects every 3h. The specimens collected were kept on ice and preserved in 10% formalin. They were weighed (Total Weight) and measured (Total Length). Sex was identified from the macroscopic analysis of gonads, which were weighed and preserved in 10% formalin. The stomachs were weighed and preserved in 70% alcohol. The environment was characterized by the multivariate analyzes. The length structure of the population, length-weight relationship, sex ratio, relative abundance and biomass were evaluated. The location and time of reproduction, size at first maturation and spawning type, were also studied. The trophic ecology was evaluated by feeding activity and content organic matter. Food items were analyzed by the methods of frequency of occurrence, degree of food preference and the feendig index. The results showed that the area downstream of the dam and lake area was greater transparency of the water in the reservoir depth and predominant amount was larger values of pH. The average length was 193.74 mm (80-258 mm ± 22.71 mm) and mean weight was 70.90 g (10- 160 g ± 23.99 g). There were significant differences in length for the periods of the year. The increase of the species was negative allometric (b = 2.34). The sex ratio was 2:1 favoring females. The relative abundance and biomass were higher in the reservoir and lake area. Spawning occurred between the months of November 2009 and January 2010, individuals preferentially spawn in the reservoir and the lake. The total spawning type and size at first maturity is from 157.5 mm. The species has iliófaga-detritivorous feeding habit with a tendency to omnivory. The feeding strategy is general, but dominant for items phytoplankton and detritus. The species H. unimaculatus, has adapted successfully to the dams and their diet may have been altered before the changes caused by the environment.